Linking taxonomy and environmental 18S-rRNA-gene sequencing of Baltic Sea protists - Majaneva, Markus (Helsingin yliopisto, 2013)
Protists are unicellular eukaryotes. Some protistan species may be impossible to distinguish under the light or even electron microscope, and a complete balanced study of protistan taxonomy requires molecular analysis and light and electron microscopy. One of the main applications of taxonomic work is the assessment of diversity of organisms in an ecosystem. However, uncertainty in taxonomic precision undermines the diversity measures. DNA sequence data provide assistance since they are easily transformed to numbers that can be compared systematically and in a similar way throughout the eukaryotic domain, using sequence similarity to define operational taxonomic units (OTUs). DNA-based assessment of diversity is called environmental sequencing. The most commonly used gene in the environmental gene sequencing for eukaryotes and also in the protistan taxonomic studies has been the small subunit (18S) ribosomal RNA gene of the ribosomal operon. Also, internal transcribed spacers (ITS) are used. The studies in this thesis were conducted with Baltic Sea protists. The Baltic Sea is a subarctic brackish-water basin that partially freezes over every winter. If the salinity of parent water is higher than 0.6, the forming ice has a semi-solid structure with solid ice crystals and saline water (brine) channels. The brine channels offer habitats for small-sized organisms. Due to the low salinity of the Baltic Sea, the brine channels are small, and therefore, the Baltic Sea ice eukaryotic community is dominated by protists. Studies on Baltic sea-ice biology have been accumulating since the 1980 s, but there are still gaps on knowledge; for example, what protistan species and how many there are associated with sea ice. In this thesis, morphological, molecular and ecological information was combined to delineate species of a Baltic Sea cryptomonad, haptophyte and dinoflagellate. Protistan community composition in Baltic Sea ice was assessed with environmental sequencing, and diversity estimates were compared in different types ...